Aggression-victimization in middle-low income students in Turkey: empathy level, gender, and grade level differences - Gürsoy, Figen (Violence and victims, 2024)
This article aimed to analyze aggression-victimization differentiation in middle-school students by empathy level, gender, and grade level. A total of 260 students living in a middle-low-socioeconomic region of Ankara, Turkey, participated in the study (mean age = 12.89, standard deviation = 0.96). Results indicated that the students were more likely to be victims of violent behaviors rather than being aggressors. We found a high probability that victims could become aggressors or vice versa. There were no significant differences between empathy and victimization-aggression. Besides, the results revealed that boys were more prone to being victims and aggressors, especially concerning physical-verbal aggression and harming properties. However, girls were more likely to be victims of isolation and—to a lesser extent—verbal aggression. We discussed these results in light of literature.